Progress and challenges in TB vaccine development - Voss, G; Casimiro, D; Neyrolles, O; Williams, A; Kaufmann, S; McShane, H; Hatherill, M; Fletcher, H (F1000Research, 2018)
The Bacille Calmette Guerin (BCG) vaccine can provide decades of protection against tuberculosis (TB) disease, and although imperfect, BCG is proof that vaccine mediated protection against TB is a possibility. A new TB vaccine is, therefore, an inevitability; the question is how long will it take us to get there? We have made substantial progress in the development of vaccine platforms, in the identification of antigens and of immune correlates of risk of TB disease. We have also standardized animal models to enable head-to-head comparison and selection of candidate TB vaccines for further development.  To extend our understanding of the safety and immunogenicity of TB vaccines we have performed experimental medicine studies to explore route of administration and have begun to develop controlled human infection models. Driven by a desire to reduce the length and cost of human efficacy trials we have applied novel approaches to later stage clinical development, exploring alternative clinical endpoints to prevention of disease outcomes. Here, global leaders in TB vaccine development discuss the progress made and the challenges that remain. What emerges is that, despite scientific progress, few vaccine candidates have entered clinical trials in the last 5 years and few vaccines in clinical trials have progressed to efficacy trials. Crucially, we have undervalued the knowledge gained from our "failed" trials and fostered a culture of risk aversion that has limited new funding for clinical TB vaccine development. The unintended consequence of this abundance of caution is lack of diversity of new TB vaccine candidates and stagnation of the clinical pipeline. We have a variety of new vaccine platform technologies, mycobacterial antigens and animal and human models.  However, we will not encourage progression of vaccine candidates into clinical trials unless we evaluate and embrace risk in pursuit of vaccine development.